Challenges Encountered in Using Learning Management System of BEEd 3rd Year Student at Bestlink College of the Philippines: Vol.3, No.2 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Two years ago, when a virus swept the country, the school started using LMS. They created this method to keep both students and educators safe. Students and teachers rely on technology to receive a high-quality education anytime and from any location, particularly during the pandemic. Students may struggle with content comprehension, internet connection, financial difficulty, motivation, and technical issues while using the LMS, yet this platform greatly assists everyone.This research investigates the issues third-year BEED students at Bestlink College of the Philippines encounter when using an LMS. The researchers used a descriptive-quantitative design and engaged randomly selected thirty (30) students to participate in the study. The main data-gathering tool was a researcher-made survey. Frequency, percentage, ranking, and an average weighted mean were used to examine the data.According to the data, content comprehension, internet, financial difficulties, and motivation are interpreted as agreeable. During the process of analyzing all of the data that the researchers have collected to find a solution to the problems that are currently happening, we will need the help of the students, teachers, and LMS provision AA to make learning possible and get rid of any problems that might get in the way of this.